2016
DOI: 10.1016/j.adolescence.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The associations between body dissatisfaction, body figure, self‐esteem, and depressed mood in adolescents in the United States and Korea: A moderated mediation analysis

Abstract: The perception of one's body image becomes particularly important in adolescence. Body dissatisfaction has been associated with negative psychological functioning, such as self‐esteem and depression. Previous findings showed that the decreased self‐esteem due to body dissatisfaction explained the association between negative attitude toward body and psychological well‐being in different cultural contexts. The present study examined adolescents from the US (N = 1002) and Korea (N = 3993) and replicated and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 68 publications
8
52
0
6
Order By: Relevance
“…It is important to note the significant differences between self‐esteem in all the BD groups regarding students with high body satisfaction. This result is consistent with those by Choi and Choi () and Franklin et al (), who found a close relationship between self‐esteem and BD, emphasising the importance of regulating this relationship in order to not cause psychological distress in adolescence. Moreover, our study showed that adolescents with BD had significantly lower perceived fitness, strength, appearance and self‐esteem than their body‐satisfied peers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is important to note the significant differences between self‐esteem in all the BD groups regarding students with high body satisfaction. This result is consistent with those by Choi and Choi () and Franklin et al (), who found a close relationship between self‐esteem and BD, emphasising the importance of regulating this relationship in order to not cause psychological distress in adolescence. Moreover, our study showed that adolescents with BD had significantly lower perceived fitness, strength, appearance and self‐esteem than their body‐satisfied peers.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown a close relationship between BD and maladaptive habits in young populations such as self‐esteem, depression and psychological well‐being (Choi & Choi, ). Although the deleterious impact of BD has been well established, the factors that increase the risk of BD are less well understood (Choi & Choi, ). BD can be subjectively tested by the Stunkard Figure Rating Scale (Carraça et al, ), which uses gender‐specific body figures.…”
mentioning
confidence: 99%
“…Body‐image is the other important antecedent to emotional wellbeing in youth, In a study of over 1600 students in grades 6 through 12, the variables of body‐image and family connectedness were statistically significant antecedents to emotional wellbeing . Other studies explored the direct relationship between body‐image and emotional wellbeing and demonstrated body‐image as a particularly significant antecedent to emotional wellbeing in youth living with and without chronic disease …”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that boys and girls may respond differently to the feelings related to body image and satisfaction. 26 Furthermore, in the first years of adolescence, gender-specific behaviors and feelings concerning body weight become more relevant. 4,27 In linear regression models, there was no association between indicators of adiposity and body esteem scores among girls older than 14 year old, possibly due to the reduced prevalence of overweight/obesity (16.4%) and high WC (8.1%) in this group.…”
Section: Discussionmentioning
confidence: 99%